-109x+5)+66=-17-17

Simple and best practice solution for -109x+5)+66=-17-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -109x+5)+66=-17-17 equation:



-109x+5)+66=-17-17
We move all terms to the left:
-109x+5)+66-(-17-17)=0
We add all the numbers together, and all the variables
-109x=0
x=0/-109
x=0

See similar equations:

| -(-x+6)=3x+2 | | 3=3c−3 | | -3+12=12x-2-11x | | 2a+2=a+24 | | 1/3(x-2)=7 | | 6=5b-2 | | -3+12=12x-211x | | 31/2b+6=30.5 | | 9x-237+6x=63 | | 11(x/4)-4(x/3)+12=2(x/3)-9(x/4) | | (6a+7)+(3a+29)=180 | | 2+3|2x-5|=9x+5 | | 4^10x-8=10^7x-9 | | 4x/3=x+10/3 | | -43-(12)=x/10 | | 16-7n=-2(1-n) | | 9x-154+3x=62 | | 2x+3(x-2)=2-4(x+3) | | 31=-6m-7 | | 2n-175=775 | | 2+1.25x=10-275x | | 5x-15-3x=10-(-3x+20) | | x4/5=8 | | 2.2x-3=31.2 | | -12=3(u-6)-6u | | 13x-6x-190=48 | | 4-g/3=4 | | -(x/3)=4 | | 3-5x+x=-7-4x | | 21-15=2(x-7) | | 4x+5=10-75x | | x-23+4x=-44-4x-50 |

Equations solver categories